2018
DOI: 10.1038/s41598-018-25098-0
|View full text |Cite
|
Sign up to set email alerts
|

Growth differentiation factor 15 ameliorates nonalcoholic steatohepatitis and related metabolic disorders in mice

Abstract: Growth differentiation factor 15 (GDF15) is an endocrine hormone belonging to the TGFβ superfamily member. GDF15 administration or GDF15 overexpression has been reported to have anti-obesity and anti-diabetic effects. Although non-alcoholic fatty liver disease (NAFLD)/non-alcoholic steatohepatitis (NASH) is frequently associated with obesity and insulin resistance, the functional role of endogenous GDF15 and therapeutic effect of GDF15 overexpression in NASH and related metabolic deterioration have not been ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
75
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 48 publications
9
75
1
Order By: Relevance
“…(40) Moreover, GDF15KO mice are also prone to develop steatosis, while GDF15-transgenic mice are protected from steatosis and associated metabolic disorders. (41) Finally, in agreement with our results, prevention of obesity in HFD-fed mice treated with recombinant GDF15 was not associated with an increase in energy expenditure, suggesting that the protective action of this hepatokine is likely driven by the reduction in food intake. (36) These considerations prompted us to directly address the role of Gdf15 in whole-body metabolic protective TAM effects.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…(40) Moreover, GDF15KO mice are also prone to develop steatosis, while GDF15-transgenic mice are protected from steatosis and associated metabolic disorders. (41) Finally, in agreement with our results, prevention of obesity in HFD-fed mice treated with recombinant GDF15 was not associated with an increase in energy expenditure, suggesting that the protective action of this hepatokine is likely driven by the reduction in food intake. (36) These considerations prompted us to directly address the role of Gdf15 in whole-body metabolic protective TAM effects.…”
Section: Discussionsupporting
confidence: 90%
“…Accordingly, GDF15KO mice are characterized by accelerated weight gain and increased fat mass, mainly localized in visceral abdominal sites, but their food intake and body weight returned to the WT level following infusion with recombinant human GDF15 . Moreover, GDF15KO mice are also prone to develop steatosis, while GDF15 ‐transgenic mice are protected from steatosis and associated metabolic disorders . Finally, in agreement with our results, prevention of obesity in HFD‐fed mice treated with recombinant GDF15 was not associated with an increase in energy expenditure, suggesting that the protective action of this hepatokine is likely driven by the reduction in food intake .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…[15][16][17] Another study in Gdf15-knockout and transgenic mice reported that GDF15 contributes to the improvement of liver fibrosis in the methioninecholine deficient (MCD) and the high fat/fructose/cholesterol (amylin) NASH models. 2,18 However, it is unclear whether this effect was due to weight loss or to direct anti-inflammatory and antifibrotic actions.…”
mentioning
confidence: 99%